Efficacy of Maxillary Expansion with Clear Aligner in the Mixed Dentition: A Systematic Review - Luca Levrini; Piero Antonio Zecca; Marina Borgese; Eleonora Ivonne Scurati; Alessandro Deppieri; Stefano Saran; Margherita Caccia; Andrea Carganico (Applied Sciences, 2025)
The purpose of this systematic review is to analyze the dentoalveolar changes resulting from the use of clear aligners in the treatment of transverse maxillary deficiency among growing children in the mixed dentition stage. An electronic literature search was carried out using the following databases: PubMed, Scopus, Cochrane Library, Embase, and Web of Science. The review protocol was prospectively registered in the PROSPERO database. Eligible studies included children aged 6 to 12 years in the mixed dentition period, presenting with erupted maxillary first molars and a transverse deficiency of the maxilla, and undergoing treatment with Invisalign® First aligners. The review encompassed various study types including retrospective and prospective designs, randomized controlled trials, preliminary studies, and case series. Two independent reviewers conducted the data extraction process. The quality of evidence was assessed using the GRADE approach. Except for studies by Bruni et al., the risk of bias in selected articles was visually summarized in a traffic light plot using the robvis tool, following the ROBINS-I methodology. For the studies by Bruni et al., a separate visual representation was created using robvis with the RoB2 evaluation framework, prepared by the authors S.E.I. and C.A. In total, 14 studies were included in the final synthesis, selected from 265 records retrieved through electronic searches and an additional 36 identified via manual screening. Several parameters were considered in order to assess dentoalveolar expansion: intercanine width, intercanine transpalatal width, intercanine dentoalveolar width, first and second interdeciduous molar width, first and second interpremolar width, first and second interdeciduous molar transpalatal width, first intermolar width, first intermolar mesial, distal, and transpalatal width, molar inclination, arch depth, and arch perimeter, and intermolar dentoalveolar width. An improvement was recorded in all parameters. The studies comparing treatment with Invisalign® First clear aligners and rapid maxillary expander highlighted that these both determined statistically significant differences compared to the natural growth group. Treatment with Invisalign® First in mixed dentition proved to be very effective for dentoalveolar expansion of the maxillary arch, with good control of the crown angulation of the upper first molar and an increase in the palatal area similar to RME, compared to pre-treatment or to the natural growth group. It could represent an effective and comfortable alternative to the traditional rapid maxillary expander treatment. However, further high-quality studies are required to support our current observations and verifying the stability of treatment outcomes on a long-term basis.